2019
DOI: 10.1093/mnras/stz2555
|View full text |Cite
|
Sign up to set email alerts
|

Power-law Sérsic profiles in hydrostatic stellar galaxy discs

Abstract: Previously, we showed that surface density profiles of the form of a power-law times a Sérsic function satisfy the hydrostatic Jeans equations, a variety of observational constraints, and the condition of a minimal radial entropy profile in two-dimensional galaxy discs with fixed power-law, halo potentials. It was assumed that such density profiles are generated by star scattering by clumps, waves, or other inhomogeneities. Here we generalize these models to self-gravitating discs. The cylindrically symmetric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…In Figure 5, the radial velocity dispersion and the vertical velocity dispersion both decline with increasing galactic radius. This decrease looks like an exponential profile and the profile agrees with the expectation made by Martinsson et al (2013) and Struck & Elmegreen (2019). More discussion on the velocity dispersion is in Section 4.4.…”
Section: Formation Of An Exponential Discsupporting
confidence: 86%
See 2 more Smart Citations
“…In Figure 5, the radial velocity dispersion and the vertical velocity dispersion both decline with increasing galactic radius. This decrease looks like an exponential profile and the profile agrees with the expectation made by Martinsson et al (2013) and Struck & Elmegreen (2019). More discussion on the velocity dispersion is in Section 4.4.…”
Section: Formation Of An Exponential Discsupporting
confidence: 86%
“…The profile evolution due to scattering can make a nearexponential disc under various initial density distributions. The appearance of a central cusp in the final profile makes the equilibrium distribution resemble a function of 1/r times an exponential, like that derived by analytic work assuming a minimum entropy gradient of the stellar system (Struck & Elmegreen 2019;Elmegreen & Struck 2016) or assuming a maximum entropy in specific angular momentum distribution (Herpich et al 2017). Marr (2020) also showed that an equilibrium galactic disc is a microcanonical ensemble with maximum entropy and that the equilibrium disc density profile is a lognormal distribution, which can fit with a near-exponential profile well.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The density profiles of all components in all the discs are compatible with an exponential form. However, we note that such a profile is imposed in the initial conditions, and therefore the convergence toward the exponential shape cannot be rigorously demonstrated here (but see Elmegreen & Struck 2013;Struck & Elmegreen 2019). Despite having a massive central clump, the gaseous components of the F25 and F40 cases yield shallower density profiles than at low gas fraction.…”
Section: Radial Profiles and The Failure Of Single-component Stabilit...mentioning
confidence: 83%
“…This well known difficulty of the CDM model is bypassed invoking physical processes which essentially shorten the timescale to reach TE, making it shorter than the Hubble time. The proposed pathways to thermalization are of very different nature (Sect 6): feedback of the baryons on the DM particles through gravitational forces [27][28][29], scattering with massive gas clumps [30,31], forcing by a central bar [32], merger of two super massive black holes [SMBHs; 26,33,34], or assuming an artificially large DM to DM collision cross section [35][36][37]. Whether or not it is collision-less, the DM seems to find a way for thermalization faster than the inefficient two-body relaxation collisions, an observational fact that weakens the original criticism.…”
Section: Purpose and Organization Of This Reviewmentioning
confidence: 99%